Enhancing cities’ resilience in the face of multiple challenges: on-going experiences in Italian and Greek cities - Limongi, Giada; Salata, Konstantina-Dimitra; Galderisi, Adriana (AESOP, 2019)
Nowadays cities are widely considered as main actors in the challenge against climate change, since they act both as generators of climate-related hazards and as vulnerable targets to their impacts. Although the issue of climate change has been for long addressed on a global scale, the key role of cities, required to translate global objectives and strategies into tailored to the site actions, is nowadays widely acknowledged. However, climate urban strategies are often largely pushed by international initiatives. This contribution focuses in particular on the 100 Resilient Cities Initiative, launched by the Rockefeller Foundation and addressed to financially support cities all over the world in developing and implementing strategies capable to increase urban resilience in order to better cope with multiple shocks and stress factors, including climate change. In detail, the contribution provides a comparative analysis of 2 selected case studies, Rome and Athens, focusing on their resilience profile, their goals and objectives, the governance of the resilience building processes (actors involved, engagement of local communities, etc.), the set of the proposed actions, highlighting strengths and weaknesses of the whole process as well as the relevance assigned to climate issues and the potential impacts of climate-related actions on cities’ resilience.
Keywords: urban resilience; climate change; 100 Resilient Cities; Rome and Athens